Phenomenological theory of the 23P state of He3 - Hinds,EA; Prestage,JD; Pichanick,FMJ (Physical Review A, 1985)
For the first time, a theory has been developed for the structure of the 23P state of He3 which is consistent with all experimental data. Using our effective Hamiltonian, containing both spin-symmetric and -antisymmetric operators, we have obtained new values for several important hyperfine parameters. The three most accurate of these are the spin-symmetric constants C, D, and E corresponding, respectively, to the contact, orbital, and tensor interactions. We find C=4283.84-0.01+0.02 MHz, D=-28.145(21) MHz, and D/E=-3.9445(21). We have also obtained improved values for other hyperfine parameters and for the orbital g factor. Our results are shown to be in agreement with ab initio calculations after making some plausible corrections for isotope and relativistic shifts. We believe that this state is now well understood at the level of 20 kHz in the interaction constants. © 1985 The American Physical Society.